2014
DOI: 10.1155/2014/792086
|View full text |Cite
|
Sign up to set email alerts
|

Potential Activity of 3-(2-Chlorophenyl)-1-phenyl-propenonein Accelerating Wound Healing in Rats

Abstract: Wound healing involves inflammation followed by granular tissue development and scar formation. In this study, synthetic chalcone 3-(2-Chlorophenyl)-1-phenyl-propenone (CPPP) was investigated for a potential role in enhancing wound healing and closure. Twenty-four male rats were divided randomly into 4 groups: carboxymethyl cellulose (CMC) (0.2 mL), Intrasite gel, and CPPP (25 or 50 mg/mL). Gross morphology, wounds treatment with the CPPP, and Intrasite gel accelerate the rate of wound healing compared to CMC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Our outcomes showed that oral administration of the respective chalcone PA to the cirrhotic rats considerably elevated the hepatic level of antioxidant enzymes SOD, CAT, and GPx by maintaining their actions at levels very close to the normative values (Figs A–C). The antioxidant capacity of PA may also be linked to its scavenging activity as well as its enhancement to the endogenous defense of hepatic cells through antioxidant enzymes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our outcomes showed that oral administration of the respective chalcone PA to the cirrhotic rats considerably elevated the hepatic level of antioxidant enzymes SOD, CAT, and GPx by maintaining their actions at levels very close to the normative values (Figs A–C). The antioxidant capacity of PA may also be linked to its scavenging activity as well as its enhancement to the endogenous defense of hepatic cells through antioxidant enzymes .…”
Section: Discussionmentioning
confidence: 99%
“…Natural chalcones and their derivatives attracted the interest of many researchers due to their bioactivity in many ailments such as anticancer , wound healing , gastroprotective , antibacterial , and anti‐diabetic . Panduratin A is one of the chalcones that was isolated from Boesenbergia rotunda rhizomes.…”
mentioning
confidence: 99%
“…A number of studies have reported the use of a large variety of medicinal plants for treating several ailments [ 8 12 ]. Andrographis paniculata (Burm.f.)…”
Section: Introductionmentioning
confidence: 99%
“…Omega-3s can lower inflammation markers in the body, contributing to heart health. 45 Inflammatory Skin Conditions.…”
Section: Heart Healthmentioning
confidence: 99%